2022
DOI: 10.3390/ijms23052697
|View full text |Cite
|
Sign up to set email alerts
|

1-Isobutanoil-2-isopropylisothiourea Phosphate, T1082: A Safe and Effective Prevention of Radiotherapy Complications in Oncology

Abstract: The radioprotective effects of a new 1-isobutanoil-2-isopropylisothiourea derivative named T1082 are presented. Research methods included toxic characteristics, radioprotective activity (Till–McCulloch’s test and 30-day survival test) in γ-ray total-body-irradiated mice, and a clinical and histological study of the effect of T1082 on acute radiation skin reactions (RSR) in rats after a single or fractionated β-ray local irradiation. T1082 is more effective than its analogue, the NOS inhibitor T1023, at low con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 34 publications
0
1
0
Order By: Relevance
“…So, some time ago, while screening linear and cyclic isothioureas, we identified and synthesized a large group of isothiourea derivatives (Figure 1A) that are competitive inhibitors of NOS (Proskuryakov et al, 2002(Proskuryakov et al, , 2005Proskuryakov et al, 2010;Filimonova et al, 2012a). Further, we found that some compounds of this group (such as T1023, T1082, T1084) are promising for further pharmacological development-as hypoxic radioprotectors that provide effective prevention of hematopoietic and gastrointestinal acute radiation syndromes, and radiotherapy complications (Filimonova et al, 2020b(Filimonova et al, , 2021(Filimonova et al, , 2022bSaburova et al, 2020), as well as antitumor, antiangiogenic agents (Filimonova et al, 2019a;2019b;2022a).…”
Section: Introductionmentioning
confidence: 99%
“…So, some time ago, while screening linear and cyclic isothioureas, we identified and synthesized a large group of isothiourea derivatives (Figure 1A) that are competitive inhibitors of NOS (Proskuryakov et al, 2002(Proskuryakov et al, , 2005Proskuryakov et al, 2010;Filimonova et al, 2012a). Further, we found that some compounds of this group (such as T1023, T1082, T1084) are promising for further pharmacological development-as hypoxic radioprotectors that provide effective prevention of hematopoietic and gastrointestinal acute radiation syndromes, and radiotherapy complications (Filimonova et al, 2020b(Filimonova et al, , 2021(Filimonova et al, , 2022bSaburova et al, 2020), as well as antitumor, antiangiogenic agents (Filimonova et al, 2019a;2019b;2022a).…”
Section: Introductionmentioning
confidence: 99%